ECOVILLAGE " VARAVĪKSNES " THE SOIL AND WATER ENVIRONMENTAL PERFORMANCE EVALUATION - Staprēns, Aleksandrs; Noviks, Gofrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Managing in agriculture with natural methods, without the use of chemically synthesized substances (fertilizers, pesticides and t.t.), can acquire organic products. Such management is a prerequisite for healthy soil and water (surface and underground), which is a diverse of fauna and flora. Rich and healthy soil is based on agriculture, which is able to resist various diseases and pests [2].Work aimed to assess the eco-village agricultural land resources of the physical-geographical, hydrological conditions and soil quality. With a view to assessing the quality of drinking water and agricultural produce low productivity reasons, it was made of water and soil sample analysis. Work report described water and soil sample analysis methods and the results obtained from the Rezekne Technology academy (RTA) laboratory. The test results will help to understand the reasons for the poor quality of samples and give recommendations to improve the quality of water and agricultural land resources.